2014
DOI: 10.1021/ci400674k
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Calculate Water Binding Free Energies in Protein–Ligand Complexes

Abstract: Water molecules are commonplace in protein binding pockets, where they can typically form a complex between the protein and a ligand or become displaced upon ligand binding.As a result, it is often of great interest to establish both the binding free energy and location of such molecules. Several approaches to predicting the location and affinity of water molecules to proteins have been proposed and utilized in the literature, although it is often unclear which method should be used under what circumstances. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 65 publications
1
58
0
Order By: Relevance
“…45,46 Notably, both studies found that Clark's equation only yielded reliable free energies when B was low. This was previously thought to be due to sampling problems.…”
Section: Free Energies Via Titrationmentioning
confidence: 98%
“…45,46 Notably, both studies found that Clark's equation only yielded reliable free energies when B was low. This was previously thought to be due to sampling problems.…”
Section: Free Energies Via Titrationmentioning
confidence: 98%
“…Moreover, the binding affinity of substrates/inhibitors may diminish if the free energy increases due to the removal of bound water molecules is not compensated by additional interactions upon their binding. 43 These water molecules are essential to represent the electrostatic behaviour of the active site, 24 helping us to answer some of our mechanistic questions. Our Quantum Chemical Cluster Approach calculations support the idea that water molecules change the electrostatic environment of the active site allowing MAO B to catalyse the studied substrates by two different mechanisms.…”
Section: Importance Of Crystallographic Water Moleculesmentioning
confidence: 99%
“…The method has the advantage of being able to identify preferred water molecule positions and at the same time rigorously calculate binding free energies in a single set of simulations. In addition, the approach naturally takes into account cooperative effects in water networks 20,22,23 . By post-processing the trajectories, it is also possible to rigorously rank order every water molecule or network in the GC region by their binding affinities.…”
mentioning
confidence: 99%